Merancang Analisis Sentimen Berdasarkan Pendapat Pengguna Aplikasi Grab Dengan Menggunakan Bahasa Pemrograman Python - Nababan, David Gibson; Sijabat, Parningotan; Danuarta, Muhammad; Damanik, Patricya (Lembaga Riset Mutiara Akbar, 2024)
In the dynamic era of digitalization, technology-based applications have seamlessly integrated into daily life, with Grab emerging prominently in the transportation and technology services sector. This study delves into the transformative journey of Grab, providing a range of services from transportation to food delivery, all while incorporating technological efficiency and user accessibility. The imperative nature of sentiment analysis for the Grab application is highlighted to comprehend user responses and experiences. Complex factors, including service quality, technological innovation, and customer interactions, shape user sentiments. The study aims to unpack key elements influencing user perceptions and emphasizes the significance of Grab's technological advancements, adaptability, and its role in societal and environmental responsibility. A profound understanding of these factors enables a contextual and holistic sentiment analysis, crucial for formulating effective corporate strategies and enhancing overall user experiences.